The Potential of the Triple Helix Model in Developing Directed Energy Weapons (DEWs) for National Defense Industry Independence - Dwipratama, Gede Priana; Rafsanjani, Wildan Akbar Hashemi (PT. Civil Military Center, 2026)
The evolution of the strategic environment shaped by the Fourth Industrial Revolution has driven the integration of emerging technologies into advanced weapon systems, including Directed Energy Weapons (DEWs). DEWs utilize focused energy forms such as lasers, microwaves, and particle beams to neutralize targets with high precision and speed. This paper explores the role of the Triple Helix Model collaboration among government, academia, and industry in advancing national defense technology, particularly DEWs, toward achieving defense industrial independence. Through literature review and policy analysis, it argues that a well-implemented Triple Helix framework can strengthen civil-military cooperation, enhance innovation capacity, and foster sustainable development of DEW technology within Indonesia’s defense ecosystem.